Microcellular antibacterial polylactide‐based systems prepared by additive extrusion with ALUM. (10th May 2019) - Amini Moghaddam, Maliheh; Stloukal, Petr; Kucharczyk, Pavel; Tow‐Swiatek, Aneta; Garbacz, Tomasz; Pummerova, Martina; Klepka, Tomasz; Sedlařík, Vladimír
Abstract : This work investigates preparation by extrusion of microcellular antimicrobial polylactide (PLA) with an additive, the latter comprising 1% potassium aluminum sulfate dodecahydrate (ALUM), and 3% or 5% of a mixture of sodium hydrogen carbonate and sodium dihydrogen phosphate (1:1). Study was made as to the properties of the materials, their hydrolysis, release profiles, and antimicrobial properties in comparison with the pure polymer. Measuring the molecular weight of samples by gel permeation chromatography revealed that, during thermal processing, the molecular weight of the PLA prepared with additives mentiond above had reduced by approximately 43%. A mechanical test confirmed a decline in mechanical properties after processing as compared with the pure PLA. Release of the antimicrobial compound and the subsequent antimicrobial activity against Staphylococcus aureus and Escherichia coli was evaluated according to ISO 22196:2007. The release of ALUM from the microcellular specimens took place in two steps. During the first 10 days, the rate of release was extremely high in contrast with the remaining period. However, the release rate of the nonporous sample was seen to equal less than 1% in the first 10 days, a phenomenon probably arising through its less active surface.